Penyelamatan ukm dari guncangan wabah sars-cov-2: Sebuah kasus dari Samarinda, Indonesia - Wijaya, Adi; Jiuhardi, Jiuhardi; Nurjanana, Nurjanana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Covid-19 does not only threaten the health aspect, but also threatens social tensions and the economic order. The existence of Small and Medium Enterprises (SMEs) is at the point of collapse. If it is not anticipated through comprehensive reform efforts, then the existence of SMEs is only a discourse and will slowly sink. This article aims to investigate the effects of the pandemic on the SMEs sector in Samarinda City. The method uses a qualitative-case study approach. Referring to the exploratory review, two points are concluded. First, the initial conditions (before Covid-19), the reputation of SMEs classified as